Identification of Dimensions, Components, and Indicators of the Educational-Behavioral Model for Socially Vulnerable Groups - MasoumBeigi, Mohammadreza; Banisi, Parinaz; Jahed, Hoseinali (Iranian Journal of Educational Sociology, 2025)
Purpose: This research aims to identify the dimensions, components, and indicators of the educational-behavioral model for socially vulnerable groups. Methods and Materials: The study was applied in terms of its objective and exploratory in nature, following a qualitative approach. The statistical population consisted of academic experts and experienced officials from universities in Tehran, who were selected using a non-random purposive sampling method. The sampling method employed in this research was stratified random sampling. Data were collected through semi-structured interviews. For assessing the internal validity of the model, as well as the external validity, a researcher-designed questionnaire derived from the model's components was used. Additionally, the criterion of trustworthiness was applied, and reliability was examined by accurately documenting the research process and ensuring alignment within and between researchers. The data analysis method used was thematic analysis (including basic, organizing, and global themes) with the Maxqda-V2018 software. Findings: The findings indicated that the educational-behavioral dimensions for socially vulnerable groups included: educational (curriculum, teaching methods, educational materials and resources, educational assessment, professional development of teachers, extracurricular activities), psychological (psychological support, psychological empowerment, mental health care, emotional support, family support), social (social support, opportunities for social participation, social awareness, enhancing social skills, promoting social solidarity, social networking), economic (job skills, entrepreneurship, local economic development, financial management education, economic empowerment), and cultural (preservation of cultural identity, cultural education, cultural communication, artistic development, protection of cultural heritage, and cultural promotion). Conclusion: Based on the identified indicators, components, and dimensions, the educational-behavioral model for socially vulnerable groups (working children in Tehran province) was designed. Finally, the internal and external validity of the model was examined, and the findings indicated appropriate validity for the designed model. Overall, the results of this study not only contribute to improving the behavior of socially vulnerable groups but can also serve as an effective tool for enhancing the quality of behavioral education for working children. This research highlights the importance of addressing the needs and changing circumstances of working children in today’s world.